Pengayaan Biodiversitas Bakteri Penangkap Cahaya Dalam Miniatur Winogradsky Yang Potensial Untuk Pengembangan Zat Warna Alamiah - Rahmat Eko Sanjaya, Ni Nyoman Tri Puspaningsih, Afaf Baktir, Ali Rohman, Purkan, Alfinda Novi Krista (FMIPA Universitas Lampung, 2022)
Natural dyes are an alternative renewable and environmentally friendly dyes. Natural dyes can be isolated from microorganisms. Winogradsky column is an enrichment culture that is suitable for obtaining various photosynthetic bacteria as sources of natural dyes. Knowledge of the Winogradsky column can be the initial stage for development of natural dyes based on microorganisms. Community service activity related to the Winogradsky column, involving chemistry and biology teachers throughout Malang Regency as partners. The activities are carried out offline at SMAN 1 Lawang and online using Zoom Meeting. The online activity also attended by SMA teachers from outside Java. The first stage of these activities were delivering material related to photosynthetic bacteria, the Winogradsky column, and dyes. The second stage was the practice of making Winogradsky columns followed by focus group discussion. The results of the questionnaire showed a positive response to the activities. The majority of participants gave a “Good” and “Excellent” rating. Participants wanted a follow-up this activity in the form of re-implementing this activity in rotation at different schools.